Profil Penyalahgunaan Napza Pada Pelajar Kelas II SLTP 5 Depok Sleman Yogyakarta - Anik Ristiyani, Suhartini dan Hendro Widagdo (Berita Kedokteran Masyarakat (BKM), 2004)
Background: The NAPZA abuse in Indonesia is especially in Yogyakarta, cause Yogyakarta as students city visited a lot of adolescent from part of Indonesia. They came to study or only enliven Yogyakarta. This is cause Yogyakarta become favourite place to illegal trade of NAPZA. Objectives: This study was aimed at finding out the sum, profile, and background of NAPZA abuse at the second year students SLTPN 5 Depok Sleman Yogyakarta.Methods: None experiment study that have the form of descriptive with cross sectional survey method. This study was carried out in Yogyakarta among the second year students of SLTPN 5 Depok Sleman Yogyakarta, and from those we got 108 respondents. It was an observational study by questionnaire (Eysisk s Inventory Questioner and special questionnaire about NAPZA). The analysis by Chi-Square test and descriptive design.Results: More than 97% of the second year students SLTPN 5 Depok Sleman Yogyakarta haven t profile NAPZA abuse. They are have enough knowledge about NAPZA and all of them againt NAPZA abuse. NAPZA abuse related with bad communication between chid-parent, and easy to get NAPZA.Keywords: NAPZA abuse, the second year students of SLTPN, bad communication, easy to get NAPZA